Comparative Examination of the Financial Status in Islamic Jurisprudence and Ethics - Ã˜Â§Ã˜Â¨Ã˜Â±Ã˜Â§Ã™Â‡Ã›ÂŒÃ™Â…Ã›ÂŒ, Ã˜Â±Ã˜ÂÃ›ÂŒÃ™Â…Ã™Â‡; Ã˜Â±Ã˜ÂÃ™Â…Ã˜Â§Ã™Â†Ã›ÂŒ, Ã˜Â¹Ã™Â„Ã›ÂŒ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
The present research inquires whether jurisprudence pays heed to the financial status of people that is created according to conventional view or rejects it altogether. The findings suggest that jurisprudence has paid heed to the rulings of financial status based on two indices of financial prosperity and personality traits. In many of these instances, a panoramic attention and accurate look at the neglected ethical propositions would unveil the conformity of ethics with jurisprudence and in other instances where the difference is obvious its reason will be analyzable and explicable in the purposes of these two sciences. This research has been performed in comparative form and with the explicatory-analytical method.